2012
DOI: 10.4025/actasciagron.v34i3.13424
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the CROPGRO model for bean (Phaseolus vulgaris L.) yield simulation

Abstract: ABSTRACT. The aim of this study was to evaluate the CROPGRO-Dry bean model for simulating dry bean yield. The model's genetic coefficients were calibrated based on the cultivars 'Pérola', 'Ouro Negro' and 'Ouro Vermelho' in Viçosa, State of Minas Gerais, Brazil. The coefficients were adjusted based on two experiments that were performed in 2003 with irrigated and nonirrigated water regimes. An additional experiment with irrigation was conducted in 2004. After calibration, the model simulated the bean yield for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…The flowering was estimated as 54 days after sowing (DAS), the onset of the first pod as 61 DAS and the physiological maturity as 96 DAS. Other studies had already proved the ability of this model in simulating the phenology of other cultivars of beans, corroborating our findings (MEIRELES et al, 2002;OLIVEIRA et al, 2012). (Figure 3).…”
Section: Model Calibrationsupporting
confidence: 81%
See 3 more Smart Citations
“…The flowering was estimated as 54 days after sowing (DAS), the onset of the first pod as 61 DAS and the physiological maturity as 96 DAS. Other studies had already proved the ability of this model in simulating the phenology of other cultivars of beans, corroborating our findings (MEIRELES et al, 2002;OLIVEIRA et al, 2012). (Figure 3).…”
Section: Model Calibrationsupporting
confidence: 81%
“…Table 3 demonstrates that the model simulated adequately crop yield, with maximum variation of 5.0%, reflecting the accuracy occurred in model calibration. OLIVEIRA et al (2012), calibrating the same model for different bean cultivars, found variations of up to 15.94% between simulated and field-observed yields. …”
Section: Model Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…COSTA et al (2015), analisando a resposta do milho à diferentes lâminas de irrigação, em Mossoró-RN, encontraram lâmina de 410 mm à 788 mm. OLIVEIRA et al (2012) comentam quanto à importância da necessidade de irrigação suplementar, mesmo em períodos em que as chuvas são mais frequentes, uma vez que há irregularidades na sua distribuição. Na Figura 5 está representada a redução esperada na produtividade potencial da água para o cultivo do milho sem o uso da irrigação suplementar, para as datas estudadas.…”
Section: Resultsunclassified